2019
DOI: 10.1177/0309524x19849860
|View full text |Cite
|
Sign up to set email alerts
|

An innovative augmentation technique of savonius wind turbine performance

Abstract: This work presents an innovative technique to enhance the performance of the Savonius wind turbine. The new technique is based on introducing an upstream deflector and downstream baffle. The shape and location of both devices are optimized using a genetic algorithm. The performance of the turbine with the optimized devices is compared with the single Savonius turbine performance. The study employs the finite volume solver (ANSYS-FLUENT) to solve unsteady Reynolds Averaged Navier–Stokes equations and turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Conversely, a vertical axis wind turbine (VAWT) is the most popular and effective device for electrical power generation from the kinetic energy of wind in urban built-up environments. These turbines are cross-flow, drag-driven wind turbines, and their power generation coefficient varies from 4% to 24% as reported in the literature [1,23,29,30]. The VAWTs are easy to manufacture and install, cheaper in price, produce less noise pollution, and can run in omni-directional winds.…”
Section: Prior Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, a vertical axis wind turbine (VAWT) is the most popular and effective device for electrical power generation from the kinetic energy of wind in urban built-up environments. These turbines are cross-flow, drag-driven wind turbines, and their power generation coefficient varies from 4% to 24% as reported in the literature [1,23,29,30]. The VAWTs are easy to manufacture and install, cheaper in price, produce less noise pollution, and can run in omni-directional winds.…”
Section: Prior Literaturementioning
confidence: 99%
“…These advantages make them more attractive than HAWTs for harnessing wind energy, but on the downside, VAWTs can not produce appreciable power when compared to HAWTs on a large scale. Hence, vertical turbines are more suitable and cost-effective when considering small-scale power generation and selfstarting at low wind speeds [25,29]. From a general perspective, the most common types of vertical axis wind turbines are the Savonius wind turbine and Darrieus wind turbine, further classifications are shown in Figure 1.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that the performance of the wind rotor decreases as the number of blades increases. To optimize the orientation of the air flow around the blades many augmentation technique have been added such as the shields (Morcos et al, 1981, Alexander & Holownia, (1978, deflector (Roy et al, 2014, Youssef et al, 2020, conveyor/deflector (Tartuferi et al, 2015), curtains (Altan & Atılgan, 2010), venting blade (Alom & Saha, 2018), deflector longitudinal (Salleh et al, 2020), V-shaped deflector (Shaughnessy & Probert, 1992), guide vane (El-Askary et al, 2015), straight deflector (Mohamed et al, 2010), they show a considerable improvement in the power of the Savonius wind turbine. The use of a straight deflector resulted in an increase in power coefficient of 27%.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the torque coefficient values at various azimuths, they also found that the peak-to-peak values in the profiles for 90 • and 135 • were less than those for 0 • and 45 • . Youssef et al (2019) introduced an upstream deflector and downstream baffle around a Savonius wind turbine and achieve a much higher power coefficient than the conventional Savonius turbine [20].…”
Section: Introductionmentioning
confidence: 99%